2009
DOI: 10.1213/ane.0b013e3181ad87b0
|View full text |Cite
|
Sign up to set email alerts
|

The Success of Emergency Endotracheal Intubation in Trauma Patients: A 10-Year Experience at a Major Adult Trauma Referral Center

Abstract: In the hands of experienced anesthesiologists, rapid sequence intubation followed by direct laryngoscopy is a remarkably effective approach to emergency airway management. An algorithm designed around this approach can achieve very high levels of success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 21 publications
1
54
0
3
Order By: Relevance
“…[12] This retrospective survey, the largest reported, confirms an overall high success rate, with no patient dying of a hypoxic cardiac arrest during airway management. Of note, a mere 21 patients required an emergency cricothyroidotomy or tracheotomy.…”
Section: Corresponding Author: M Berry (Michaelberry1@nhsnet)supporting
confidence: 61%
See 2 more Smart Citations
“…[12] This retrospective survey, the largest reported, confirms an overall high success rate, with no patient dying of a hypoxic cardiac arrest during airway management. Of note, a mere 21 patients required an emergency cricothyroidotomy or tracheotomy.…”
Section: Corresponding Author: M Berry (Michaelberry1@nhsnet)supporting
confidence: 61%
“…Of note, a mere 21 patients required an emergency cricothyroidotomy or tracheotomy. [12] Despite obvious limitations to this study (retrospective, specialist trauma centre, resource-rich setting), the results are compelling.…”
Section: Corresponding Author: M Berry (Michaelberry1@nhsnet)mentioning
confidence: 88%
See 1 more Smart Citation
“…Our study revealed that four of 554 trauma patients (0.72%) received ESA in emergency surgery settings (odds ratio: 28.9-144.1). In the field of emergency medicine, studies have found that 0.3-0.9% of trauma patients received CTY in pre-hospital or ER settings [3][4][5][6]. Severe facial injury patients received ESA more often than did patients with other types of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Eğer hava yolu sağlanmasında; resüsitatif çabalar içinde acil ETE gereksinimi yoksa, hastanın hava yolunu güçlük olasılığına göre değerlendirmek için zaman vardır. Zorluk, hastanın işbirliğine, maske ile havalandırılabilmesine, supraglottik hava yolu gereci yerleşimine, laringoskopi, ETE ve cerrahi hava yolu sağlamadaki zorluklara bağlı olabilir (24) .…”
Section: Introductionunclassified